Recent results from NA61/SHINE - Rybicki Andrzej (EPJ Web of Conferences)
The NA61/SHINE experiment at the CERN SPS is a multipurpose fixed-target spectrometer for charged and neutral hadron measurements. Its research program includes studies of strong interactions as well as reference measurements for neutrino and cosmic-ray physics. A significant advantage of NA61/SHINE over collider experiments is its extended coverage of phase space available for hadron production. This includes the nearly entire forward hemisphere for charged hadrons and additionally, a large part of the backward hemisphere for specific neutrals. This paper summarizes a selected set of new results, obtained by NA61/SHINE since the last SQM conference (Busan, 2022). Particular attention is devoted to (1) the first-ever direct measurement of open charm production in nucleus-nucleus collisions at SPS energies (2) the difference observed between charged and neutral meson production in Ar+Sc reactions, up to now not understood by existing models, and (3) the importance of baseline effects in the search for the critical point of strongly interacting matter.